Answer:
g(x) = (x + 6)^2 - 5
Step-by-step explanation:
To translate f(x) to the left by 6 units, replace x with x+6.
To translate f(x) down 5 units, replace f(x) with f(x)-5.
Together, these replacements give you ...
... g(x) = f(x+6) -5
... g(x) = (x +6)^2 -5
The first graph is what i would think
9514 1404 393
Answer:
-203.1875
Step-by-step explanation:
The ends of the interval are ...
(-4, g(-4)) = (-4, 1023 15/16)
(1, g(1)) = (1, 8)
The average rate of change is the slope of the line between these two points:
m = (y2 -y1)/(x2 -x1)
m = (8 -(1023 15/16))/(1 -(-4)) = (-1015 15/16)/5 = -203 3/16
The average rate of change on the interval is -203 3/16.
Five hundred six thousand seven hundred nine.
. The series is divergent. To see this, first observe that the series ∑ 1/kn for n = 1 to ∞ is divergent for any integer k ≥ 2.
Now, if we pick a large integer for k, say k > 100, then for nearly all integers n it will be true that 1 > cos(n) > 1/k. Therefore, since ∑ 1/kn is divergent, ∑ cos(n)/n must also be divergent The *summation* is divergent, but the individual terms converge to the number 0.<span>by comparison test since cosn/n <= 1/n is convergent
and 1/n is divergent by harmonic series
so the series is conditionally converget </span>